Perspektif Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak Terhadap Pekerja Di Bawah Umur (Studi Kasus Di Desa Kota Bangun, Kecamatan Ranomeeto, Kabupaten Konawe Selatan) - Nur Hayaty (Jurnal Syariah Hukum Islam, 2019)
ABSTRAC The main problem in this study are how the fact about underage workers in kota bangun village and how the prespective of the children protection law in article 76I for underage workers in kota bangun villages this study aims to find out the facts that have happened to works in the age of the elderly and to find out perspective of the cildren protection law in article 76I for underage workers in kota bangun villages Qualitative description research type. the research subject were underageworkers and their parents. Data collection technicques used participant observation. there are 5 underage workers working in the informal sector who lose their education rights and work more then 3 hours an a day with and without receive wages. the perspective of the child protction law in article 76I provides a ban on exploitation of children but employer place them to do work and there are not sanction for employers. The implementation of the child protction law in article 76I has not been not realized properly so there is no legal protection for underage workers The role of the goverment, law enforcement provides information to parents as entreprereurs related child protection. The author hopes to underage work